Legalitas dan Mekanisme Crowdfunding Syariah dalam Perspektif Hukum Islam - Hana Reswara Ardiana; Baidhowi Baidhowi (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The development of digital technology has brought various innovations to the financial system, one of which is sharia crowdfunding. As a form of technology-based fundraising based on sharia principles, this mechanism aims to avoid elements of usury, gharar, and maysir which are prohibited in Islam. This article discusses the legal aspects and operational mechanisms of sharia crowdfunding from the perspective of Islamic law and regulations in Indonesia. By using a qualitative research method based on literature analysis, sharia crowdfunding has a strong legal basis through the fatwa of the National Sharia Council-Indonesian Ulema Council (DSN-MUI) and the regulations of the Financial Services Authority (OJK). In practice, sharia crowdfunding uses various contracts such as mudharabah, musyarakah, and wakalah bil ujrah to ensure fair and transparent transactions. Although it has promising prospects, challenges such as lack of sharia financial literacy, limited specific regulations, and digital security aspects are still major obstacles in its implementation. Therefore, collaboration between regulators, industry players, and the community is needed to encourage a more inclusive and sustainable sharia crowdfunding ecosystem.